Membangun Kesadaran Kolektif tentang Bahaya TPPU dan TPPT - Aras Prabowo, Muhammad; Umam, Fuadul; Lutfa, Asna; Yasik, Fatkhu; Mubayyinah, Fira; Khotimah, Khusnul; Erfandi, Erfandi; Qodir, Abdul; Nurhidayat, Samsul; Fitri Aryani, Habsyah (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
This community engagement research aims to build collective awareness among young people regarding the dangers of money laundering (TPPU) and terrorism financing (TPPT) through the “Diskusi Kontemporer GEMA APUPPT” program at Universitas Nahdlatul Ulama Indonesia (UNUSIA). The program is designed as a literacy and advocacy movement that positions students not merely as objects of socialization, but as agents of change. The study employs a participatory action research approach with mixed methods, using pre-test and post-test instruments, participatory observation, in-depth interviews, and focus group discussions. The activities involve cross-stakeholder collaboration, including PPATK, financial institutions, and the academic community. The findings indicate a significant increase in participants’ knowledge and critical attitudes toward the concepts, modes, and impacts of TPPU/TPPT, alongside the growth of legal and ethical awareness grounded in Aswaja values and maqāṣid al-sharīʿah. Students began to demonstrate the ability to identify suspicious transaction patterns in digital spaces, refuse invitations to become money mules, and promote integrity-based financial practices through digital campaigns. This study concludes that the GEMA APUPPT model is effective as a prototype of a campus youth movement for the prevention of TPPU/TPPT and has the potential to be replicated in other higher education institutions as part of a national education program against financial crime.